(untitled) (Research, Society and Development, 2021)
The fluvial regime of a river represents the volume variation of the water during a period, being an essential tool for the study of water availability. In this sense, this study aimed to characterize the fluvial water regime of the Acre river basin, considering the space-time dynamics to study its water availability. The average, the maximum and minimum annual and monthly flows were identified, which were obtained through statistical treatment of the fluviometric data of five stations along the Acre river, made available by ANA (National Agency for Water and Basic Sanitation). It was verified that the period of highest water availability, for the historical series studied, occurred between December and April, while the period with lower average monthly flows occurred between June and September.